KOMPETENSI PEDAGOGIK GURU PAUD TENTANG PENCEGAHAN KEKERASAN SEKSUAL ANAK BERKEBUTUHAN KHUSUS SEKOLAH INKLUSI - Taufiqi Azulva, Naula; Oktavianingsih, Eka; Oktavianingsih , Eka (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Sexual violence against children has shown an increasing, with higher levels of vulnerability among children with special needs in inclusive schools due to limitations in communication, cognitive abilities, and dependence on adults. This condition requires early childhood education (ECE) teachers to function not only as educators but also as child protectors through adequate pedagogical competence. This study aims to analyze the pedagogical competence of ECE teachers in preventing sexual violence against children with special needs in inclusive schools, focusing on the mastery of children’s characteristics, learning planning, dialogical learning implementation, and learning outcome evaluation. This research employed a qualitative approach using a case study method conducted at TK Anna Husada Bangkalan, involving 10 ECE teachers who teach children with special needs. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that understanding children’s characteristics is the most dominant aspect of pedagogical competence and plays a crucial role in preventing sexual violence, supported by integrated learning planning and dialogical, educative learning implementation. However, the use of learning technology remains suboptimal. Therefore, this study recommends strengthening the pedagogical competence of inclusive ECE teachers and enhancing the use of learning media as a preventive child protection strategy